(untitled) (Jagannath University Journal of Arts, 2026)
This study examines the political consciousness embedded in the novels of Humayun Ahmed, focusing on how his fiction reflects and reframes major historical crises in Bangladesh, such as the Partition, the 1971 Liberation War, military regimes, and post-independence disillusionment. Instead of overt political commentary, Ahmed employs subdued realism and psychological nuance to depict the tension between individual lives and state machinery. His characters are often caught in moral and ideological conflicts that mirror broader national anxieties, offering readers a deeply humanized lens through which to understand political trauma. The research adopts a qualitative methodology, drawing on contextual and textual analysis to uncover how his narratives function as literary responses to political events. Ultimately, this study argues that Ahmed’s fiction serves as a parallel archive of Bangladesh’s socio-political history, where memory, resistance, and identity are negotiated through narrative. His work thus demonstrates literature’s enduring power to engage with and critique state violence and historical silencing. Jagannath University Journal of Arts, v-15, i-2, 2025:p40-55